Pattern Of Adolescent Learning Hindu Scholarship Recruits Through Pasraman Widya Dharma Saraswati - I Nyoman Warsana (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2017)
Mental development and religious personality is one aspect that needs to get special attention because through it children and adolescents understand the meaning of Religion and its benefits for human life and will later form a person who virtuous noble character. Having grown a noble personality then the teenager has a fortress to face the challenges of his life. In an effort to provide guidance to the younger generation, Parisada Hindu Dharma in Atula Village and Hindu community together attempt to form the path of non-formal education of Hinduism namely Pasraman Widya Dharma Saraswati.